Food habits of Hoplobatrachus tigerinus (Daudin, 1802), Limnonectes nepalensis (Dubois, 1975) and Bufo stomaticus L ũtken, 1862 (Amphibia: Anura) in Pokhara Valley - Parajuli, Yub Raj; Budha, Prem Bahadur; Shah, Karan Bahadur (Journal of Natural History Museum, 2008)
A total of 118 specimens (2 frog and 1 toad spp.) were collected and examined for their food habits. All anurans were found primarily insectivorous but their preferences varied as stomach contents of Limnonectes nepalensis (100%, Bufo stomaticus (91.7%) and Oplobatrachus tigerinus (73.1%) were found with insect food. All sampled anurans were found primarily relied upon coleopteran, hymenoptera, mollusca, hemiptera however, some species-specific preference was also noted e.g. H. tigerinus mostly depended upon orthoptera, mollusca and myriapoda, B. stomaticus on hymenoptera and coleopteran and L. nepalensis on hemiptera. Collembolan and diptera. Most of these insects are notorious agricultural pests therefore, the findings strongly support the positive role of the anurans in agro-ecosystem. J. Nat. Hist. Mus. Vol.22, 2005 p.134-139